Minimally Invasive Image-Guided Procedures for Benign Liver Lesions - Khan, Fiza M.; Nezami, Nariman; Stumpf, Florian; Smith, Tyler A.; Revizin, Margarita; Fang, Adam; Loya, Mohammad F.; Sheth, Rahul A.; Yevich, Steven; Habibillahi, Peiman (Digestive Disease Interventions, 2023)
As access to affordable high-resolution medical imaging has improved, so too has the identification of benign hepatic lesions. Advanced imaging techniques and applications often allow characterization of these lesions so as to differentiate benign and malignant lesions without the need for biopsy. Patients with benign liver lesions are usually asymptomatic; however, a palliative intervention may be indicated if a benign liver lesion is symptomatic. This article reviews the characteristic imaging features of benign liver lesions, the indications for minimally invasive intervention, and the specific procedures for minimally invasive, nonsurgical intervention, and the procedural expectations, effectiveness, and periprocedural care.
Keywords: hemangioma; focal nodular hyperplasia; hepatic adenoma